PHYSICAL ENVIRONMENTAL INFLUENCES ON SILICOSIS: A NARRATIVE REVIEW INTEGRATING COMMUNITY EXPOSURE AND WISTAR RAT EXPERIMENTAL FINDINGS IN COAL-HANDLING REGIONS - Mustika Fatimah; Irsan Saleh; Susila Arita; Legiran (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Coal mining, handling, and transportation activities are major sources of airborne particulate matter containing respirable crystalline silica, which poses significant risks to respiratory health. Silicosis remains a serious occupational and environmental disease affecting not only workers but also communities living near coal-handling areas. Physical environmental factors, including air quality, temperature, humidity, and wind speed, play an important role in influencing dust generation, dispersion, and inhalation exposure. This narrative review aims to synthesize current evidence on the influence of physical environmental conditions on silica exposure and silicosis development, integrating findings from environmental monitoring studies, epidemiological research, and experimental Wistar rat models. A literature search was conducted using major scientific databases to identify relevant peer-reviewed articles published between 2010 and 2024. The reviewed evidence indicates that prolonged or high-intensity exposure to silica dust is strongly associated with chronic pulmonary inflammation and progressive fibrosis. Environmental conditions can exacerbate exposure risk by increasing airborne particulate concentrations and respiratory vulnerability. Experimental studies using Wistar rats provide mechanistic insights into silica-induced lung injury, supporting epidemiological observations in human populations. This review highlights the importance of integrating environmental, occupational, and biological perspectives to improve risk prediction, early detection, and preventive strategies for silicosis in coal-handling regions.